SUITABLITY AND CARRYING CAPACITY OF KARTINI BEACH JEPARA AS COASTAL TOURISM DESTINATION - Achmad Fama; . Haeruddin; Frida Purwanti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Kartini beach as a marine tourism in Jepara, Central Java that have beach attraction consist of natural environment area suitable for tourism. Its potency have opportunity to be developed as marine ecotourism. The current problem is increasing number of visitor each year that might degrades the environment. The aims of this reseacrh are to analyse tourism suitability and to assess carrying capacity of the Kartini Beach as beach tourism. This research was conducted in Desember 2016 – March 2017 at the Kartini Beach of Jepara. The methods uses analysis of land suitablity for beach recreation and carrying capacity analysis. The result shows that suitability index in location 1 to 3 are suitable with value about 48 % – 60 % as beach recreational area. The results of carrying capacity analysis of location 1 with total area of 0,22 ha is 176 people / day, location 2 with total area of 0,1 ha is 80 people / day, and location 3 with total area of 0,13 ha is 104 people / day. The conlusions of this reseacrh are Kartini beach is suitable for beach recreation and the number of visitor has esceeds the ability of carrying capacity. Keywords: beach tourism, land suitablity, carrying capacity, Kartini beach, Jepara